2012
DOI: 10.1021/ie301031u
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Based Nanoparticles for Toxic Organic Degradation: Silica Platform and Green Synthesis

Abstract: Iron and iron oxide nanoparticles (NPs) are finding wide applications for the remediation of various toxic chloro-organic compounds (such as trichloroethylene, TCE), via reductive and oxidative processes. In this study, Fe NPs (30-50 nm) are synthesized by reduction from ferric ions immobilized (by ion exchange) on a platform (two types of sulfonated silica particles), in order to prevent the NP agglomeration. Next, the Fe NPs are oxidized and their effectiveness for the oxidative dechlorination of TCE via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Magnetic metal-ceramic nanocomposites, consisting of a dispersion of transition metal (TM = Fe, Co, Ni) nanoparticles into a ceramic matrix, are being actively studied in view of a variety of applications associated with their porous structure, ranging from environmental issues (e.g., water remediation [45][46][47], treatment of pollutants [48][49][50][51][52]) to catalysis [53][54][55][56] and biomedicine [57,58]).…”
Section: Ceramic Nanocompositesmentioning
confidence: 99%
“…Magnetic metal-ceramic nanocomposites, consisting of a dispersion of transition metal (TM = Fe, Co, Ni) nanoparticles into a ceramic matrix, are being actively studied in view of a variety of applications associated with their porous structure, ranging from environmental issues (e.g., water remediation [45][46][47], treatment of pollutants [48][49][50][51][52]) to catalysis [53][54][55][56] and biomedicine [57,58]).…”
Section: Ceramic Nanocompositesmentioning
confidence: 99%
“…It was found that MB degradation in the Fe 3 O 4 /Mn 3 O 4 /rGO/PMS system is well formulated by a pseudosecond-order kinetics (Eq.1). The result is shown in Table 2 41,42 . The relationship between reaction rate and temperature reveals that the PMS activation process is an endothermic reaction: higher temperature would drive the reaction to produce more 15 active sulfate and hydroxyl radicals and thus enhance the MB degradation efficiency.…”
Section: Effect Of Different Operating Parameters On the Catalytic Acmentioning
confidence: 99%
“…In the last decade, the scientific interest towards magnetic nanostructured / nanocomposite materials has steadily increased owing to their functional properties associated with widespread applications ranging from electronics [1], magneto-optics and photocatalysis [2][3][4][5] to supercapacitors [6,7], hyperthermia [8], drug delivery [9,10], water remediation [11], energy harvesting [12]. Oxides of transition metals / rare earths have received particular attention because of the concurrence of magnetic effects and semiconducting-like properties [3,12,13] Magnetic metal-ceramic nanocomposites, consisting of a dispersion of Fe 0 , Co 0 , or Ni 0 nanoparticles into a prevailingly amorphous silica and alumina ceramic matrix, are an important sub-class of nanomaterials whose fields of application are typically associated with their porous structure, which makes them particularly suitable for use in environmental protection [14][15][16][17][18][19][20][21][22], catalysis [23][24][25][26][27][28] and biomedicine [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%